Efficiency measurement model of projects using DEA - Ku-Mahamud, Ku Ruhana; Abd Ghani, Nor Farzana; Mat Kasim, Maznah; Abdullah, Fader (2010)
This paper presents the efficiency measurement model that has been developed based on data envelopment analysis. The model is intended for products produced by organization, optimizes a ratio of multiple weighted outputs to a multiple weighted inputs, where the efficient unit will have a score of one, and the inefficient unit will have a score less than one. The model is simple yet practical in implementation. Descriptive analysis of the data, model validation and relative efficiency results are presented. It is anticipated that the projects which act as the decision making unit can later be used to determine the efficiency of the company department/unit that housed the projects.